1986
DOI: 10.3133/pp1325
|View full text |Cite
|
Sign up to set email alerts
|

Ground-water hydrology and subsurface migration of radionuclides at a commercial radioactive-waste burial site, West Valley, Cattaraugus County, New York

Abstract: Test holes and wells 12 Stratigraphy and general groundwater movement at the burial site 14 Physical and hydraulic properties of the till 20 Physical and mineralogical properties 20 Hydraulic conductivity 20 Anisotropy 2 3 Fractured zone 23 Lenses of sorted material 23 Extent and continuity 23 Hydraulic conductivity 29 Equivalent hydraulic conductivity of the till 29 Groundwater flow at the burial site 30 Flow within the till 30 Flow within the underlying lacustrine unit 32 Computer simulation of groundwater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…Hendry (1982) reported values of about 10 -5 to 10 -7 cm sec -1 for field tests of till in southern Alberta. Prudic (1986) reported hydraulic conductivity values of 10-s cm see-t for clayey till in New York, and Bradbury et al (1985) reported values of 10 -9 cm sec -j for clayey till in northern Wisconsin. Both of the latter studies were of till that has a higher clay content than the till in the north-central prairies.…”
Section: The Effect Of Physical and Hydraulic Characteristics Of Tillmentioning
confidence: 99%
“…Hendry (1982) reported values of about 10 -5 to 10 -7 cm sec -1 for field tests of till in southern Alberta. Prudic (1986) reported hydraulic conductivity values of 10-s cm see-t for clayey till in New York, and Bradbury et al (1985) reported values of 10 -9 cm sec -j for clayey till in northern Wisconsin. Both of the latter studies were of till that has a higher clay content than the till in the north-central prairies.…”
Section: The Effect Of Physical and Hydraulic Characteristics Of Tillmentioning
confidence: 99%
“…Neglecting unsaturated zone processes is not considered appropriate in arid regions, where the thickness of the unsaturated zone can reach hundreds of meters and water recently recharged at the top of the unsaturated zone may not ever reach the water table given current climate conditions. Furthermore, there are notable examples where the unsaturated zone was explicitly included in watershed scale transient models in humid climates (Freeze 1972a, 1972b; Prudic 1981; Winter 1983; Smith and Hebbert 1983; Lee 2000; Vanderkwaak and Loague 2001; Jones et al 2006). However, when the unsaturated zone is included, these efforts commonly used a fully coupled saturated‐unsaturated flow approach based on Richards’ equation (Richards 1931; Freeze 1971; Reeves and Duguid 1975; Frind and Verge 1978; Yeh 1987; Vanderkwaak 1999; Panday and Huyakorn 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Downward water flow rates are thus on the same order as the hydraulic conductivity of the till. Under these low flow rates diffusion becomes the dominant transport mechanism for water dissolved radionuclides (Prudic, 1986). However, an alternative pathway may exist whereby contaminants migrate laterally through the fractured, upper layer of the till.…”
Section: Introductionmentioning
confidence: 99%
“…As the disposal pits fill with water, contaminants could move upward into the upper fractured zone and from there travel laterally through this more permeable zone to nearby streams or other exposure points. A number of groundwater modeling studies of the FDA and adjacent state-licensed disposal areas have been conducted previously (Prudic, 1986;U.S. DOE, 1986;Bergeron and Bugliosi, 1988).…”
Section: Introductionmentioning
confidence: 99%